E-learning Modules for Clinical Teachers (Out of Print) - Judy McKimm; Tim Swanwick; Helen Halpern; Caroline Elton; Nav Chana; Doug Parkin; Clare Morris; Sam Held; Adam Feather; Jenny Firth-Cozens; Helen Webb; Dulcie Brake (Association of American Medical Colleges, 2009)
Abstract This resource is a series of web-based open-access e-learning modules covering a range of topics essential for clinical teachers and supervisors. The modules were developed by the London Deanery to inform and support the professional development of clinical teachers. Topics include the following: assessing educational needs, setting learning objectives, small-group teaching, how to give feedback, supervision, careers support, workplace-based assessment, facilitating learning in the workplace, diversity, equal opportunities and human rights, introduction to educational research, improving one's lecturing, appraisal, teaching clinical skills, managing poor performance, involving patients in clinical teaching, and interprofessional education. The modules are written in an easily accessible style and are up-to-date and referenced with appropriate literature. Each module has defined learning outcomes and is designed to be stand-alone, although there are cross-references from module to module where appropriate. Some sections of some modules relate specifically to the unique UK context (e.g., the specific requirements for supervision or appraisal), but each module also contains much that is generic and can be used in a range of contexts. Faculty developers have also used the modules as support material for face-to-face teaching or as web links to other open learning resources. Self-assessment activities are included for each module to help put learning into practice, and on completion, a certificate can be printed out for use in revalidation or relicensing. Each module is supported by additional literature and downloads on various topics. The modules do not cover every aspect of clinical teaching and learning: We have tried to be realistic and develop resources that can be used by individuals in their own time and at their own pace but also that faculty and educational developers can use, either in part or as a whole to support their own clinical teaching. These resources provide a starting point of engagement for many jobbing clinicians and aim to stimulate thinking about clinical teaching in terms of people's professional development, but they are not intended to be the full story.